Design, Synthesis and Biological Evaluation of Novel Diaryl Pyrazole Derivatives as Anticancer Agents - Nourmahammadi, Jalal; Moghadam, Ebrahim S.; Shahsavari, Zahra; Amini, Mohsen (Letters in Organic Chemistry, 2020)
Cancer is one of the major causes of mortality all around the world. Globally, nearly 1 in 6 deaths is due to cancer. Researchers are trying to synthesize new anticancer agents. Previous studies demonstrated that some pyrazole derivatives could be considered as potential anticancer agents. Herein, ten novel derivatives of 1,5-diarylpyrazole were synthesized in four step reactions and cytotoxic activity was investigated by MTT cell viability assay. All of the compounds were characterized by 1H NMR and 13C NMR and their purity was confirmed by elemental analysis. The cytotoxicity was determined against three cancerous cell lines (HT-29, U87MG and MDA-MB 468) and AGO1522 as a normal cell line. Compound 5a showed the best cytotoxic activity on cancerous cell lines in comparison to paclitaxel. Annexin V/ PI staining assay also showed that compounds 5a and 5i would lead to significant apoptosis induction in MDA-MB 486 cell line.
Keywords: Drug research